Determination of Hop Oil Content by Steam Distillation According to IOB Method 6.3: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Biendl, M. (BrewingScience, 2002)
The EBC Analysis Committee has tested the IOB Method 6.3 "Hop Oil Content of Hops and Hop Products" by collaborative trial. In winter 2000/2001 this collaborative trial was conducted using three samples of hop pellets with different hop oil levels in the range 0.4 ? 2.3 ml/100 g. Five members of the EBC Analysis Committee and one member of AHA (Arbeitsgruppe Hopfenanalyse) took part in the collaborative trial. All participants used a distillation still manufactured by "Normschliff" (article number: 8503000) which is identical to the still as specified in the British Pharmacopoeia and recommended in the IOB Method 6.3.